Penerapan School Based Vector Control (SBVC) untuk Pencegahan dan Pengendalian Vektor Penyakit di Sekolah - Nur Siyam; Widya Hary Cahyati (Faculty of Public Health, Hasanuddin University, Makassar, 2018)
Efforts to achieve a healthy school free vectors need to be improved because of the increasing number ofvector-transmitted diseases such as scabies, dermatitis, diarrhoea, typhoid, and dengue in students. Steps that canbe taken to establish a clean and healthy lifestyle in preventing and controlling the disease vector breeding eitherby implementing the School-Based Vector Control (SBVC) in school. Application of this SBVC emphasis on awarenessand concern of students in the control and the creation of a healthy environment. The research objective is theestablishment of a model SBVC and gets an idea of the effectiveness of the model SBVC as improving the PHBs andthe creation of a healthy environment to the students. The research was done in SMP Islam Sultan Agung 4, Semarang.The study population was all students of SMP Islam Sultan Agung 4 Semarang. Samples are students whohave health problems and unhealthy as many as 30 students. This type of research is a Quasi-Experiments withnon-randomized design one group pretest-posttest design. The data collection is done by observation, interviews,and questionnaires. The instrument of research is observation checklists and questionnaires. Univariate and bivariatedata analysis by Wilcoxon statistical test. The results showed indicators of personal hygiene, hygiene inthe classroom, cleanliness in toilets and ablution and cleanliness in the schoolyard before and after application ofSBVC increased significantly (p <0.05). So that a clean and healthy living behaviour in students in the preventionand control of vector at school increased significantly (p = 0.00).